Factors that Influence Auditor Decisions: Ethics, Experience, and Culture with Materiality as an Intervening Variable - Ladewi, Yuhanis (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to determine and analyze the effect of professional ethics, auditor experience, and organizational culture on auditor decision-making, considering the level of materiality as an intervening variable at the Supreme Audit Agency of the Republic of Indonesia, Representative of South Sumatra. Data was obtained from a questionnaire distributed to auditors working at the Badan Pemeriksa Keuangan. The results of this study indicate that professional ethics and auditor experience affect materiality level considerations. Organizational culture has no significant effect on materiality level considerations, professional ethics, and materiality level considerations have a significant effect on auditor decisionmaking, and auditor experience and organizational culture have no significant effect on auditor decision-making.